2020
DOI: 10.1007/s11906-019-1011-2
|View full text |Cite
|
Sign up to set email alerts
|

The Renin-Angiotensin System in the Central Nervous System and Its Role in Blood Pressure Regulation

Abstract: Purpose of the Review The main goal of this article is to discuss how the development of state-of-the-art technology has made it possible to address fundamental questions related to how the renin-angiotensin system (RAS) operates within the brain from the neurophysiological and molecular perspective. Recent Findings The existence of the brain RAS remains surprisingly controversial. New sensitive in situ hybridization techniques and novel transgenic animals expressing reporter genes have provided pivotal inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 118 publications
0
60
0
2
Order By: Relevance
“…In this context, PRR can initiate its own signaling pathway and induce its pro-oxidative effects ( Labandeira-Garcia et al, 2017 ). Although it was shown that there is a relationship between PRR and neural development ( Trepiccione et al, 2016 ), RAS-independent functions of PRR within the brain are not yet clear ( Nakagawa et al, 2020 ).…”
Section: Structure Of the Brain Renin–angiotensin Systemmentioning
confidence: 99%
“…In this context, PRR can initiate its own signaling pathway and induce its pro-oxidative effects ( Labandeira-Garcia et al, 2017 ). Although it was shown that there is a relationship between PRR and neural development ( Trepiccione et al, 2016 ), RAS-independent functions of PRR within the brain are not yet clear ( Nakagawa et al, 2020 ).…”
Section: Structure Of the Brain Renin–angiotensin Systemmentioning
confidence: 99%
“…Ang-II, in turn, elicits its downstream physiological effects predominantly via the AT 1 R. However other components of the RAS can counter-regulate the ACE-Ang-II-AT 1 R pathway such as ACE2, Ang-(1-7), Mas receptor (MasR), alamandine, and the Mas­related G protein­coupled receptor member D (MrgD) ( Santos et al, 2003 ; Santos et al, 2018 ; Arendse et al, 2019 ; Paz Ocaranza et al, 2020 ). All RAS components have been identified in both central (brain) ( De Kloet et al, 2016 ; De Kloet et al, 2017 ; Nakagawa et al, 2020 ) and periphery (kidney, blood vessels, heart, adrenal gland) ( Fyhrquist and Saijonmaa, 2008 ).…”
Section: Physiology Of Ras and Cytokines In Hypertensionmentioning
confidence: 99%
“…Following the elucidation of the components of the classic RAS, comparable elements were identified in many body organs including the brain. The so-called brain RAS is associated with neurons, astrocytes and microglia functions in a paracrine, autocrine, and even intracrine signaling role ( Huber et al, 2017 ; Jackson et al, 2018 ; Nakagawa et al, 2020 ). Many CNS nuclei (i.e., the LT, PVN, RVLM, NTS and AP) implicated in cardiovascular control and fluid balance are rich in AT1-R-positive cells and are often innervated by axons containing some components of the RAS ( Sumners et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%